Evaluation of Neurodevelopmental Screening Test Scores in Children with Vitamin B12 Deficiency - Tanc, Ceren; Yildiz, Ismail (Neuropediatrics, 2023)
Introduction Vitamin B12 deficiency can lead to hematological findings, neurological symptoms, and neurodevelopmental delay. The aim of this study was to investigate the impact of vitamin B12 deficiency on the neurodevelopment of children.Materials and Methods This study included 89 children aged between 6 and 24 months without any complaints; 44 of these were evaluated in the study group (serum vitamin B12 <300 pg/mL) and 45 in the control group (serum vitamin B12 ≥300 pg/mL). Denver Developmental Screening Test II (DDST-II) and the Social Communication Area Screening Test (SCAST) were evaluated in each participant.Results The mean vitamin B12 level in the study group was 206.11 ± 9.1 pg/mL, and in the control group, it was 540.65 ± 24.1 pg/mL. When DDST-II results were analyzed, the rate of getting suspicious and abnormal results in the study group was significantly higher compared with the control group (p = 0.001). The rate of the “risky” SCAST results of the cases was found to be statistically significantly higher in the study group than in the control group (p = 0.003). Vitamin B12 values of patients with suspicious or abnormal DDST-II results and with risky SCAST results were found to be statistically significantly lower than those with normal neurodevelopmental screening tests results (p = 0.001 and p = 0.001, respectively).Conclusion Vitamin B12 deficiency can lead to neurodevelopmental delay in children, even in the absence of neurological and hematological symptoms or complaints, which highlights the importance of early detection and intervention of vitamin B12 deficiency.
Keywords: vitamin B12 deficiency; neurodevelopment; Denver Developmental Screening Test; Social Communication Area Screening Test